ANALISIS POTENSI, EFEKTIVITAS, DAN EFISIENSI RETRIBUSI PARIWISATA SEBAGAI SUMBER PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN KLATEN TAHUN 2011 – 2015 - Danyanto, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of this study were: 1) to analyze the potential retribution Klaten district tourism from 2011 - 2015. 2) to analyze the effectiveness of retribution tourism in Klaten regency of 2011 - 2015. 3) analyze the efficiency of retribution tourism in Klaten regency of 2011 - 2015. 4) to analyze the contribution of the tourism levy Revenue in the District of Klaten from 2011 - 2015. The research method using the case study method, the type of data used quantitative and qualitative data, the data source used secondary data. Data collection methods used documentation. Data analysis technique used is descriptive analysis. In conclusion: 1) The potential of real retribution Klaten district tourism from 2011 - 2015 which in 2011 amounted to Rp 1.283.640.000,00, 2012 amounting to Rp 1.476.330.000.00, in 2013 amounting to Rp 625.572.000,00, 2014 amounting to Rp 765.300.000.00, 2015 amounting to Rp 827.022.000,00 and the average real potential retribution Klaten district tourism from 2011 - 2015 in the amount of Rp 995,572,800.00. The real potential retribution biggest tourism attractions that exist in the Fountain Clark (OMAC) and the real potential of the tourism levy receipts smallest on Tomb Objects Ronggowarsito. 2) The calculation of the effectiveness of retribution Klaten district tourism from 2011 - 2015, namely in 2012, 2014 and 2015 was very effective, because the value obtained is still above 100%. For the year 2011 amounted to 68,72% categorized as ineffective, in 2013 amounted to 79,29% in the category less effective. The average value of the tourism levy effectiveness ratio in the district of Klaten the years 2011 - 2015 amounted to 91,57% in the category is quite effective. 3) The calculation of efficiency retribution Klaten district tourism from 2011 - 2015 as very efficient for intervals of less than 10% efficiency. 4) Contributions levy tourism on regional revenue in Klaten regency of 2011 - 2015 which in 2011 amounted to 1,01%, in 2012 implanted at 1,03%, in 2013 by 0,88%, in 2014 amounted to 0,91% and in 2015 amounted to 0,63%, with an average contribution of tourism levy to the original income Klaten Regency year 2011 - 2015 of 0,89%. Tourism levy contribution to regional revenue Klaten Regency Year 2011 - 2015 are all in the category of contribution is very less due to enter the category from 0,00 to 10,00%.Keywords: Potency, Effectiveness, Efficiency, Tourism Levy, Local Revenue